Pengaruh Pemberian Neurosensorimotor Reflex Integration Pada Perubahan Hiperaktivitas Anak Dengan Autism Spectrum Disorder (ASD)) - Dwi Livia Sari; Yohanes Deo Fau; Angria Pradita; Achmad Fariz (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Autism Spectrum Disorder (ASD) is a developmental disorder that causes social dullness and hyperactive behavior in children that is difficult to control. This study aims to analyze the level of hyperactivity in children with Autism Spectrum Disorder (ASD) before and after Neurosensorimotor Reflex Integration.